Gender Dynamics in the Adoption of Climate Adaptation Practices: A Case Study in the Cauca Department of Colombia - Devereux, T. (2014)
The study concludes that the perceptions of men and women differ substantially, as to which CSA practices are considered more beneficial. In addition, the study identifies traditional gender roles in agricultural activities and considerable gender gaps in terms of ownership of resources. Furthermore, an examination of how information is diffused throughout the region reveals certain inequalities in the method and degree to which information reach men and women. The vast majority of both male and female farmers seem familiar with the concept of climate change and had perceived its effects in the watershed. However, while most of the interviewed women stated that they had modified at least some of their activities due to these changes, less than half of the interviewed men had done so, suggesting that women may be more exposed or vulnerable to changes in climate, or alternatively, that their productive activities are more affected.